Arctic Regional Governance: Actors and Transformations - Obydenkova, Anastassia (Politics and Governance, 2024)
This thematic issue analyzes recent and ongoing changes in Arctic regional governance in new geopolitical, security, and socio-economic contexts. It places current challenges in the Arctic within a historical context, aspiring to identify solutions, and enhances our understanding of modern processes. It presents three perspectives on Arctic regional governance: the first focuses on the challenges to Arctic environmental governance (marine living resources and Arctic seals); the second looks at the role of large nation-states, such as Russia and China, in Arctic regional governance; and the third one analyses the challenges posed to Indigenous people - in Russia, Finland, and Canada. Many overlapping themes are developed in the articles: historical lessons (e.g., from the Cold War period), challenges to the inclusiveness of environmental governance, and the role of cross-border diffusion and learning. New challenges to Arctic regional governance in the context of the war in Ukraine affect environmental governance, international scientific collaboration, and the lives of Indigenous people. Yet we know little about the depth of these recent transformations. This thematic issue aims to fill in at least some of the outlined gaps.